Correction: Potential public health impacts of gonorrhea vaccination programmes under declining incidences: A modeling study. - Lin Geng; Lilith K Whittles; Borame L Dickens; Martin T W Chio; Yihao Chen; Rayner Kay Jin Tan; Azra Ghani; Jue Tao Lim (PLoS Medicine)
[This corrects the article DOI: 10.1371/journal.pmed.1004521.].